2014
DOI: 10.1089/sur.2013.069
|View full text |Cite
|
Sign up to set email alerts
|

Infection of a Rathke Cleft Cyst: A Rare Cause of Pituitary Abscess

Abstract: Predisposing factors for pituitary abscesses in primary lesions include immunosuppression and pituitary irradiation, surgery, or infarction. Approximately one-third of pituitary abscesses arise within other lesions. The clinical manifestations are non-specific. Magnetic resonance imaging shows a cystic lesion with central low intensity and rim enhancement after administration of contrast. When a pituitary abscess is diagnosed, surgical procedures should be performed promptly via a transsphenoidal (preferably) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Furthermore, the PPBS positive rate has been demonstrated to be significantly lower in RCC patients compared with that in normal individuals (16), suggesting that the cyst has an effect on the posterior pituitary and pituitary stalk. Additionally, it has been reported that inflammatory responses are present within certain cases of RCC (6,20). The current study revealed that the PPBS+ rate was significantly lower in RCC patients with inflammatory responses than those without.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the PPBS positive rate has been demonstrated to be significantly lower in RCC patients compared with that in normal individuals (16), suggesting that the cyst has an effect on the posterior pituitary and pituitary stalk. Additionally, it has been reported that inflammatory responses are present within certain cases of RCC (6,20). The current study revealed that the PPBS+ rate was significantly lower in RCC patients with inflammatory responses than those without.…”
Section: Discussionmentioning
confidence: 99%
“…Common symptoms of symptomatic RCCs include headache, vision loss, visual field defects and pituitary endocrine dysfunction (4). Uncommon symptoms include meningitis (5), pituitary abscess (6) and intracranial aneurysms (7). RCCs can be slow or acute in onset (7).…”
Section: Introductionmentioning
confidence: 99%
“…[1214] Pituitary abscess formation within RCC does not usually result in significant diabetes insipidus. [15,16] Panhypopituitarism is rare in RCC though patients with symptomatic RCC usually have pituitary dysfunction of varying degrees. [17–19] In our case, the endocrine work-up results revealed panhypopituitarism resulting in adrenal insufficiency, hypothyroidism, and gonadal failure.…”
Section: Discussionmentioning
confidence: 99%
“…[15,28] The limitation of our case was that routine cytology test and bacterial culture were not conducted, though the pathological test showing no inflammation cell infiltration partially proved the lesion not to be infectious. The clinical progression of our patient mainly included symptomatic deteriorations, severe hyponatremia, and consciousness disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…Rim enhancement with contrast on T1WI is generally considered diagnostic of pituitary abscess but also can be detected in RCC, especially in infected RCC. [23] It is difficult to distinguish pituitary abscess and infected RCC according to MRI features alone. Pituitary abscess is rare and usually causes severe DI, hypopituitarism, and headache,[4] whereas the hormone levels were normal in our patient.…”
mentioning
confidence: 99%